2015
DOI: 10.1590/0103-8478cr20150219
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular fractures of traumatic etiology in dogs: 955 cases (2004-2013)

Abstract: (tarsus, carpus, metacarpus, metatarsus and phalanges (n=57)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
6
10
0
2
Order By: Relevance
“…Radius bone carries the heavier weight of the fore limb compared with the ulna in dogs therefore is more susceptible for fractures than ulna (2). The traumatic injuries which result from traffic accidents, fighting, fall, gunshot and explosive projectiles are the main causes of distal radial fractures (3). Reduce blood supply of distal radius region with little of soft tissues enveloping the fractured site, considered as the most important factors contributes for delayed or incomplete healing of distal radial fracture (2).…”
mentioning
confidence: 99%
“…Radius bone carries the heavier weight of the fore limb compared with the ulna in dogs therefore is more susceptible for fractures than ulna (2). The traumatic injuries which result from traffic accidents, fighting, fall, gunshot and explosive projectiles are the main causes of distal radial fractures (3). Reduce blood supply of distal radius region with little of soft tissues enveloping the fractured site, considered as the most important factors contributes for delayed or incomplete healing of distal radial fracture (2).…”
mentioning
confidence: 99%
“…This finding is in agreement with Simon et al (2010) who found that femoral fractures were more common due to the fact that the distal half of the femur is away from the long axis of the pelvic limb making it more susceptible to bending forces leading to fractures. Libardoni et al (2016), in a larger sample size retrospectively studied, over a 10-year period reported that tibia and fibula fractures were next in incidence to femoral fractures. In our 10-month study, we observed a similar pattern of higher incidence of femoral fractures but next in incidence were radio-ulnar fractures.…”
Section: Resultsmentioning
confidence: 89%
“…Retrospective and prospective studies are essential to determine prevalence of diseases in a particular geographic location (Chaves et al, 2014). It also helps clinicians to improve the diagnosis and treatment of common ailments in any Veterinary Teaching Hospital (an example of a tertiary veterinary institution) (Libardoni et al, 2016). Ideally, a tertiary Veterinary establishment should be equipped with facilities that will make it function effectively in the diagnosis, treatment and care of animal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic events are the main cause of orthopedic disorders in dogs and cats (STREETER et al, 2009;ELZOMOR et al, 2014), and fractures result mainly from car accidents (VIDANE, 2014), ballistic projectiles, fights, and falls (KUMAR, 2007). High incidence of car accidents was due to the high number of both animals with access to public roads, and owners who suppress the containment and protection measures in their homes and during outings (LIBARDONI et al, 2016).…”
Section: Resultsmentioning
confidence: 99%